Environmental Aspects in High-Rise Buildings - Abduvalievich, Abduvaliev Timur; Islamovich, Kushnazarov Pulat (European Journal of Life Safety and Stability (2660-9630), 2021)
For ensuring comfort conditions of staying and habitation, high-rise buildings have a significant amount of engineering equipment, operation of which significantly damages the human environment. Architects and specialists working in the sphere of high-rise building construction make great efforts to reduce the negative effect of high-rise buildings on the ecology. The passive measures include the creation of atriums in the building that ensures natural lighting and ventilation in the premises without the use of engineering equipment. Active measures for reducing the negative impact on the environment include the use of renewable sources of energy: wind turbines, solar units, terrestrial heat, bio-fuel. All this leads to the significant reduction in the energy consumption from urban networks. The generation of this energy is connected with processing of natural fuel and emission of the great amount of carbon oxide. All active and passive methods are aimed at reducing the level of impact on the ecological situation and, finally, at the preservation of natural riches of the environment.